Implementasi Media Pembelajaran Spinning Wheel sebagai Upaya Mengembangkan Public Speaking Skill dalam Mata Pelajaran Bahasa Inggris pada Peserta Didik Kelas X Program Kesetaraan Paket C di SKB Negeri Surabaya - Putri, Fina Akmalia; Rosyanafi, Rofik Jalal (J+PLUS UNESA, 2024)
Learning that takes place during English subjects for class X students at Surabaya State Learning Activities Studio tends to be passive and less interactive. An alternative solution to this problem is implementing spinning wheel learning media. Spinning wheel learning media is a flexible learning media where the application can be in the form of a 2D plane which can be designed using a word wall website according to the needs of tutors, students and learning materials. This research aims to describe and analyze the implementation of the spinning wheel learning media as an effort to develop public speaking skills in the English subject of class X students in the package C equality program Surabaya State Learning Activities Studio. The research method used is a qualitative descriptive method with data collection techniques of in-depth interviews, documentation, participant observation and field notes. The results obtained by class X students experienced significant changes and developments in their public speaking skills after implementing the spinning wheel learning media with a combination of varied learning models and methods.